Positive approaches to conflict at work - Tan, Suzanna (Routledge, 2026)
How can we sensitively manage different types of conflict to create a more harmonious and efficient workplace?Workplace conflict can arise when people with different backgrounds or values disagree on approaches, interests, and ideas. This can result in inefficient collaboration and may even impact workers' mental health. This book covers a range of scenarios around how conflict at work can manifest and discusses approaches to managing these in the right way to improve motivation, productivity, and the overall well-being of employees. It explores contemporary research, theory, and models, and includes exercises for critical reflection to aid understanding. In so doing, it encourages leaders to take responsibility for addressing different types of conflict and how to do so with sensitivity. It also signals when other approaches, such as coaching, mentoring and mediation may be necessary and, when appropriate, signposts to internal formal processes such as disciplinary and grievance procedures.This accessible and practical book assists business owners, managers, and leaders in effectively navigating conflict management within the work environment.
Keywords: Conflict management.; elektronické knihy; electronic books